MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MENGGUNAKAN PEMBELAJARAN KOOPERATIF MODEL STAD MATERI SAKRAMEN TOBAT PADA KELAS VIII C SEMESTER DUA TAHUN PELAJARAN 2021/2022 - Yuliatri, Margaretha (Persatuan Guru Republik Indonesia Kota Semarang, 2022)
Group learning activities can help spur active learning. Teaching through small group cooperative activities will make it possible to promote active learning activities in a special way. What students discuss with their friends and what students teach their friends allow them to gain understanding and mastery of the subject matter. This research is based on the problem: How is the effect of STAD cooperative learning on the Sacrament of Penance material on students' learning motivation? How is the improvement of student learning outcomes in the Sacrament of Penance material with the implementation of the STAD cooperative learning model? While the purpose of this study was to determine the increase in students' motivation and learning outcomes in the Sacrament of Penance with the implementation of STAD cooperative learning. This study used two cycles of classroom action research, each cycle consisting of four stages, namely: design, activity and observation, reflection, and revision. The target of this research is grade VIII C students in the second semester of the 2021/2022 academic year. The data obtained are in the form of observation sheets and the results of teaching and learning activities. From the results of the analysis with the implementation of the STAD cooperative learning model, it was found that the motivation of learning activities and student learning outcomes increased from cycle I to cycle II, student activity increased from 61%, 77%, 80%, and 86% learning outcomes increased classical completeness 50% to 88% and the value of the first cycle of 79.25 increased in the second cycle to 86.50%. The conclusion of this study is that STAD cooperative learning can have a positive effect on motivation and learning outcomes of VIII C students, and this learning model can be used as an alternative learning for Budi Pekerti Catholic Religious Education.